1998
DOI: 10.1103/physrevlett.81.558
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Modeling Delay Feedback Systems

Abstract: Systems with delayed feedback can possess chaotic attractors with extremely high dimension, even if only a few physical degrees of freedom are involved. We propose a state space reconstruction from time series data of a scalar observable, coming along with a novel method to identify and model such systems, if a single variable is fed back. Making use of special properties of the feedback structure, we can understand the structure of the system by constructing equivalent equations of motion in spaces with dimen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
107
0
7

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(116 citation statements)
references
References 15 publications
2
107
0
7
Order By: Relevance
“…Recent studies on prediction address system identification and model development [7], as well as the use of anticipated synchronization between coupled identical systems [8]. In this work, we demonstrate that synchronization of a numerical model to an experimentally measured waveform allows us to both forecast the future dynamics of a high-dimensional system and estimate the local maximum Lyapunov exponent and its distribution.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Recent studies on prediction address system identification and model development [7], as well as the use of anticipated synchronization between coupled identical systems [8]. In this work, we demonstrate that synchronization of a numerical model to an experimentally measured waveform allows us to both forecast the future dynamics of a high-dimensional system and estimate the local maximum Lyapunov exponent and its distribution.…”
mentioning
confidence: 74%
“…In networked sensor arrays designed to detect spatiotemporal disturbances, prediction methods could enable efficient acquisition and incorporation of data from multiple sensors [5]. In biomedical treatment, prediction models could lead to improved strategies for adjusting drug dosage and delivery or physiological control [6].Recent studies on prediction address system identification and model development [7], as well as the use of anticipated synchronization between coupled identical systems [8]. In this work, we demonstrate that synchronization of a numerical model to an experimentally measured waveform allows us to both forecast the future dynamics of a high-dimensional system and estimate the local maximum Lyapunov exponent and its distribution.…”
mentioning
confidence: 99%
“…As it is stated in ref. [17] the Kaplan-Yorke dimension of this system is D KY ∼ 13.5, which, according to the Kaplan-Yorke conjecture, D KY = D 1 , for a typical attractor. We have made a standard reconstruction analysis over time series of up to 16384 data points.…”
Section: A Generalized Mackey-glass Systemmentioning
confidence: 99%
“…In order to investigate how our algorithm work on high dimensional systems, we use a generalization of the Mackey-Glass (MG) equation [17], a delayed feedback system,ẋ…”
Section: A Generalized Mackey-glass Systemmentioning
confidence: 99%
“…Two widely applied techniques are the autocorrelation function (ACF) and the delay mutual information (DMI) [14] . Other techniques include the phase information [15] , the minimal forecast error [16] , the filling factor analysis [17] , the permutation-information theory [18] , and the extrema interval analysis [19] . In 2010, we found that the TD signature could be identified through observing the RF power spectral and observing its fine structure [20] .…”
mentioning
confidence: 99%